2013
DOI: 10.3233/rnn-120286
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of body representations after surgical arm elongation in an achondroplasic patient

Abstract: Purpose: A realistic body representation needs to be constantly updated. In case of physiological modifications, body representations integrate information coming from different sensory sources, including the sense of touch. Previous studies described transient modifications of these representations following illusory distortions. In this single case study, we documented the changes occurred in lower-level, primary somatosensory, and higher-level representations, in a case of upper arms elongation. Method: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…This reinforces the hypothesis that, as the body cannot biologically shrink, the BS can only extend, but never changes in the opposite direction (Bassolino et al, 2014 ; Cardinali, Brozzoli, et al, 2009 ; de Vignemont et al, 2005 ; but see Ganesh et al, 2014 ; Miller et al, 2014 ). Several studies have established that after surgical extension of limbs in achondroplasic patients, body representations, namely the BS and the explicit BI, were modified toward a “normalization” when compared to body-typical subjects (Cimmino et al, 2013 ; Di Russo et al, 2006 ). The PPS also appeared enlarged (Cimmino et al, 2013 ), as the physical length of the arm is known to correlate with some spatial processes at a distance (Longo & Lourenco, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reinforces the hypothesis that, as the body cannot biologically shrink, the BS can only extend, but never changes in the opposite direction (Bassolino et al, 2014 ; Cardinali, Brozzoli, et al, 2009 ; de Vignemont et al, 2005 ; but see Ganesh et al, 2014 ; Miller et al, 2014 ). Several studies have established that after surgical extension of limbs in achondroplasic patients, body representations, namely the BS and the explicit BI, were modified toward a “normalization” when compared to body-typical subjects (Cimmino et al, 2013 ; Di Russo et al, 2006 ). The PPS also appeared enlarged (Cimmino et al, 2013 ), as the physical length of the arm is known to correlate with some spatial processes at a distance (Longo & Lourenco, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established that after surgical extension of limbs in achondroplasic patients, body representations, namely the BS and the explicit BI, were modified toward a “normalization” when compared to body-typical subjects (Cimmino et al, 2013 ; Di Russo et al, 2006 ). The PPS also appeared enlarged (Cimmino et al, 2013 ), as the physical length of the arm is known to correlate with some spatial processes at a distance (Longo & Lourenco, 2007 ). Thus, we think we should be careful when choosing the tasks, inputs, and outputs that we use when studying body and space representation plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…The topological map of the body (TMB) was assessed using the Frontal body-evocation subtest (FBE) of the Body Representation Test (Daurat-Hmeljiak et al., 1978; Cannoni and Tega, 2009). This task is still largely used in its original and adapted versions both in clinical and experimental settings over the life span to study alterations in the mental representation of the relations between body parts (e.g., Guariglia et al., 2002; Marangolo et al., 2003; Di Russo et al., 2006; Canzano et al., 2011; Cimmino et al., 2013; Fuentes et al., 2013; Palermo et al., 2014; Bassolino et al., 2015; Di Vita et al., 2015, 2017; Spitoni et al., 2015; Zantedeschi and Pazzaglia, 2016; Perez-Marcos et al., 2018). Task materials included a small plastic board on which the position of the head was depicted as a reference part, and nine tiles, each representing a body part.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Serino and colleagues found that participants responded 36 ms earlier when the target was accompanied by a near as compared to a far sound. Using very similar methods, distance-dependent modulations of tactile RTs were also reported by Bassolino et al (2010), Serino et al (2011), and Cimmino et al (2013). Using a range of different but related methods, similar effects have often been reported (Serino 2019).…”
Section: Introductionmentioning
confidence: 59%
“…In experiments presenting one of two unchanging sounds at two distances, far sounds controlled for near sounds (Bassolino et al 2010;Cimmino et al 2013;Kitagawa et al 2005;Serino et al 2007Serino et al , 2011Tajadura-Jiménez et al 2009;Teramoto et al 2013). By contrast, in experiments using two speakers, the relative intensity of each speaker was adjusted to produce a 'looming' (increasing intensity of near relative to far), or 'receding' sound (increasing far relative to near, Ardizzi and Ferri 2018;Canzoneri et al 2012Canzoneri et al , 2013aFerri et al 2015a;Maister et al 2015;Serino et al 2015;Teneggi et al 2013).…”
Section: Control Conditionsmentioning
confidence: 99%